The Optimization of a Dimenhydrinate Transdermal Patch Formulation Based on the Quantitative Analysis of In Vitro Release Data by DDSolver through Skin Penetration Studies - Bazigha K. Abdul Rasool; Amira A. Mohammed; Yasmein Y. Salem (MDPI AG, 2021)
Dimenhydrinate is an over-the-counter medication that is used to relieve nausea, vomiting, and vertigo caused by motion sickness. It has a short elimination half-life, possibly due to its first-pass metabolism. The current study aimed to prepare and evaluate new transdermal formulations of dimenhydrinate to prolong the drug's release and improve its cutaneous permeation. First, the patches were fabricated and evaluated to determine their properties. The results were statistically investigated and considered significant at the p < 0.05 level. Additionally, the quantitative analysis of the drug-release data and kinetic modeling was performed by using the DDSolver software to decide the candidate formula dependably. The effect of the penetration enhancers on the permeability of dimenhydrinate from the selected patch was then studied ex vivo compared to the control sample, and the patch's safety was evaluated in rabbits, using the skin-irritation test.